Effect of alkali earth metal doping on the CuO/Al₂O₃ oxygen carrier agglomeration resistance during chemical looping combustion - Liu, Guicai (2022)
The influence of alkali earth metals (AEMs, including Ca, Sr and Ba) doping on the performance of CuO/Al2O3 oxygen carrier (OC) in chemical looping combustion (CLC) was investigated. The OCs using solid-state synthesis method were evaluated in a fluidized bed reactor using municipal solid waste (MSW) syngas as fuel for 50 redox cycles. It was found that the doping of AEMs enhanced the CLC performance on CuO/Al2O3. XRD characterization and TGA analysis showed that aluminates of AEMs were formed in the doped OCs leading to the segregation of CuO from CuAl2O4 spinel, thereby promoting the redox kinetics. The OCs doped with AEMs exhibited enhanced stability and agglomeration resistance throughout multiple redox cycles in the fluidized bed experiments. CuO/Al2O3 containing 40 wt% CuO suffered from severe agglomeration and deactivation during initial 5 cycles, while the OCs with Ba, Sr and Ca doping respectively deferred the agglomeration to 15-20th, 20-25th and >50th cycle. 5–10 wt% Ca-doping content exhibited great stability without deactivation or agglomeration issues during 50 cycles, but excess Ca doping (≥20 wt%) showed severe agglomeration. The agglomeration was attributed to the outward migration of Cu/CuO, leading to the segregation from CuAl2O4 and surface enrichment. The enhanced agglomeration resistance with AEM doping was mainly attributed to outward migration of AEM species and inward migration of Cu species during the synthesis process.